IMPLEMENTASI PROGRAM KKN BERBASIS MASJID DALAM PENGEMBANGAN KESEJAHTERAAN SOSIAL DAN RELIGIUS DESA SUKASARI - Hanif, Padlim; Amirullah , Sidik; Maharani , Suci; Thahara , Asven; Trianingsih , Jepti; Riani , Nenti Reda; Rosiana , Rosiana; Monika , Nales; Elmi , Elmi; Sari , Mela Okta Berian; Nopia , Meksa (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The community in Sukasari Village, Air Periukan District, Seluma Regency, faces significant challenges in enhancing both social and religious welfare. These issues include low participation in religious activities, limited awareness of the dangers of drug abuse among adolescents, and a lack of community initiatives in maintaining environmental cleanliness. This study aims to implement a mosque-based Community Service Program (KKN) to address these issues by integrating social and religious activities. The program includes activities such as 1 Muharram competitions, regular mosque cleaning every Friday, drug abuse awareness campaigns at local junior high schools, TPQ teaching, weekly Saturday health exercises, village hall cleaning, tote bag decorating workshops, and leading Friday prayers. A participatory approach was used, involving the community in all stages of the program. Data was collected through direct observation, structured interviews, and questionnaires, and analyzed qualitatively. The results show a significant increase in community engagement in both religious and social activities, contributing to improved social cohesion and religious values. The findings suggest that a well-structured mosque-based program can effectively enhance the welfare of the community both socially and spiritually.